2004
DOI: 10.1038/sj.npp.1300583
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Nicotine Administration Results in Biphasic, Brain-Specific Changes in Kynurenate Levels in the Rat

Abstract: The content of the endogenous NMDA and a7 nicotinic acetylcholine receptor antagonist kynurenate (KYNA) is increased in the cerebral cortex and cerebrospinal fluid of patients with schizophrenia. In view of the very high incidence of smoking in schizophrenic individuals, a study was designed to examine the effect of acute and prolonged nicotine administration on brain KYNA levels in experimental animals. Adult male rats received subcutaneous nicotine injections twice daily for up to 10 days, and animals were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…It has also been shown that common cyclooxygnease-2 (COX-2) inhibitors, such as parecoxib, decrease KYNA concentration. 63 Relatedly, there is evidence that nicotine can alter KYNA concentration 64 supporting the possibility that nicotine may be used by persons with schizophrenia to counter cognitive deficits induced by KYNA. Thus, the development of kynurenergic compounds as adjunctive therapies for psychosis may also be useful in combating co-occurring psychopathology and substance abuse.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that common cyclooxygnease-2 (COX-2) inhibitors, such as parecoxib, decrease KYNA concentration. 63 Relatedly, there is evidence that nicotine can alter KYNA concentration 64 supporting the possibility that nicotine may be used by persons with schizophrenia to counter cognitive deficits induced by KYNA. Thus, the development of kynurenergic compounds as adjunctive therapies for psychosis may also be useful in combating co-occurring psychopathology and substance abuse.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also controlled by the cortical glutamatergic input to the dopaminergic neurons in the VTA. Local infusion in the rat striatum of a kynurenine hydroxylase inhibitor has been shown to increase extracellular levels of dopamine, which were decreased by the addition of KYNA to the perfusate (390, 391). The association between low levels of KYNA and increased levels of dopamine has also been observed in mice with a null mutation in the gene that encodes the KATII enzyme (516).…”
Section: Figures and Tablesmentioning
confidence: 99%
“…KA, an endogenous antagonist for NMDA and α7 nicotinic acetylcholine receptor, is dramatically increased in rat hippocampus, striatum, and frontal cortex, but not in the serum by prolonged (for 10 days) subcutaneous injections or osmotic minipumps of nicotine. Nicotine has no effect on Kyn in brain or blood [87]. There is no report about the effect of smoking on KP and its function in CVD.…”
Section: Abnormal Kp and Risk Factors For Cvdmentioning
confidence: 99%